Internet‐enabled Tourism Entrepreneurs. International Entrepreneurial Values Elicited through Repertory Test and Laddering Analysis. (4th July 2012) - Glavas, Charmaine; Pike, Steven; Mathews, Shane
ABSTRACT Although the tourism industry has been dramatically altered due to the Internet, there has been limited research published about international entrepreneurial values and Internet use in tourism firms. The findings of this study point to a relationship between the values of Internet‐enabled international entrepreneurs in small‐sized to medium‐sized enterprises and the inclination of the firm to develop and initiate international activity. The findings of this study suggest that Internet‐enabled tourism entrepreneurs share similar construct values. Two effective but underutilized qualitative methods were used in this study. The first method, repertory test, is an efficient technique for exploring constructs in decision making; the second method, laddering analysis, facilitates understanding of the perceived consequences and personal values guiding behaviour. Copyright © 2012 John Wiley & Sons, Ltd.